Synthesis of Two Novel Azilsartan Cocrystals: Preparation, Physicochemical Characterization and Solubility Studies - Lei Gao; Xian-Rui Zhang (Crystals, 2020)
Azilsartan is a novel angiotension II receptor blocker primarily used to treat high blood pressure. This is not a formulation-friendly molecule largely due to the inherent water-solubility pitfalls. In this paper, two novel cocrystals of azilsartan (AZ) were studied (AZ-BIP, AZ-BPE; BIP = 4,4′-bipyridine, BPE = trans-1,2-bis (4-pyridyl) ethylene) by solution crystallization. The structures of these two cocrystals were characterized by powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA), including the single-crystal structure determination of AZ-BIP and AZ-BPE. In the cocrystals AZ-BIP (2:1) and AZ-BPE (2:1), two AZ molecules and one coformer formed a sandwich structure through N-H…N interactions. These sandwich structures were extended into a one-dimensional structure through O-H…N hydrogen bonds. The equilibrium solubility study demonstrated that the AZ-BIP and AZ-BPE cocrystals both showed higher solubility than azilsartan in water.